The essence of readiness of the personality to self-educational activity - Martyniuk, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article is a theoretical analysis of scientific development problems of readiness of students to self education and the problems of the methods of scientific psychological research and summarizing the data. The unit of analysis singled out: the nature study methods readiness to self education and individual aspects, diagnostic capabilities of these methods. Generalization obtained in the analysis of the results is based on the evaluation of the usefulness of specific diagnostic methods on key indicators of readiness of students to self education. The conclusion is that today the question remains the method of ascertaining the presence of self-identity in general, its characteristics, the method of determination of the willingness of the individual to exercise such activities. The idea of the feasibility of a written interview techniques and analysis of products for ascertaining the presence of individual self education in general, its characteristics; and experimental method for determination of the willingness of the individual to exercise self education.